Government Finance Statistics : Compilation Guide for Developing Countries. (Manuals and Guides; MG, 2011)
The Government Finance Statistics: Compilation Guide for Developing Countries represents a new approach by the IMF's Statistics Department (STA) to assist developing countries to compile government finance statistics (GFS) in accordance with the guidelines of the Government Finance Statistics Manual 2001 (GFSM 2001). The Guide specifically addresses issues relevant to developing countries. The Guide is based on our experience over many years of technical assistance and training to member countries, addressing common problems they face, and answering questions that often arise. Examples, figures, and tables are used to facilitate the reader's understanding of the topics discussed.